Exploring the relationship between work–family conflict and sleep disturbance: a study on stratification and interaction - Lee, Jian; Oh, Juyeon; Park, Heejoo; Sim, Juho; Lee, Jongmin; Kim, Yangwook; Yun, Byungyoon (Frontiers in Psychology, 2023)
Introduction: Despite several studies on the association between work-family conflict (WFC) and sleep disturbances, a more comprehensive approach considering occupational factors is lacking. We aimed to analyze this association among Korean workers and the combined effects of WFC and job-related factors on sleep disturbance. Methods: Data on paid workers from the 6th Korean Working Conditions Survey were analyzed. Odds ratios (ORs) with 95% confidence intervals (CIs) for sleep disturbances with WFC were calculated using a multiple logistic regression model among Korean workers. Furthermore, stratification and interaction analyses were conducted between WFC and socioeconomic factors related to sleep disturbance. Result: Among the 24,923 workers (male: 11,752, female: 13,171) examined, 35.40% of males and 39.95% of females experienced sleep disturbances. In both sexes, the WFC group was significantly associated with sleep disturbance (adjusted OR (95% CI): male, 2. 90 [2.67-3.16]; female, 2.54 [2.35-2.74]). According to the stratification analysis, the association between sleep disturbance and WFC was prominent among younger and highly educated individuals, those engaged in quick returns, and larger companies in both sexes. In the interactions between WFC, quick return, occupation, and company size on sleep disturbance, there were significant additive associations, except between WFC and occupation among female workers.This study highlights the association between WFC and sleep disturbances in male and female workers and emphasizes the importance of maintaining work-life balance.